IDENTIFICATION OF YOUNG STAR OBJECTS NEAR DUST BUBBLE N10 - Nazar, A.B.; Alimgazinova, N.Sh.; Kyzgarina, M.T.; Demessinova, A.M.; Manapbayeva, A.B. (Recent Contributions to Physics, 2022)
Over the past decade, the most important observations of the interstellar medium have been made in the infrared and radio regions of electromagnetic radiation. Of particular interest were GLIMPSE (Galactic Legacy Infrared Midplane Survey Extraordinaire), MIPSGAL and WISE (Wide-field Infrared Survey Explorer) surveys of several areas of star formation. Distinctive features of the infrared view of the Galactic disk at wavelengths from 3.4 μm to 22 μm include regions of ionized hydrogen HII, infrared bubbles, young stellar objects, massive star formation, infrared dark clouds, diffuse dust, include hydrocarbons and radiation from millions of stars. Based on current literature, infrared signatures in hot regions around young massive stars have been identified as dust bubbles, so in this paper, the regions around bubble N10, one of the northern infrared bubbles included in Churchwell’s catalog, were investigated. Using archival data from the WISE and 2MASS catalogs, we searched for candidates for young stellar objects around the N10 dust bubble and found 117 emission objects. Koenig et al. (2014) plotted diagrams of their color indices and energy distribution in the spectrum for each studied object under different classification conditions. According to the results of studies around the infrared dust bubble N10, objects at an early stage of evolution were discovered: 13 objects are young class I stars and 13 objects are young class II stars, 3 objects are classified as transitional disks.